How Philippine Nationalist and Neo-Imperialist Political Identities Influence Foreign Policy: Examining the Case of Palestine - Susan Kurdli; Andre Gonzales (Universitas Islam Internasional Indonesia (UIII), 2025)
The discourse on the ongoing escalation of conflict in Gaza has signaled a shift in the stance of the international community on the question of Palestinian statehood. As discourses, and subsequently policies, shift, we investigate the sources and implications of specific policies. In this paper, we look at the Philippines, a democracy with a long anti-colonial history, and examine why its foreign policy has called out Israel’s crimes against Palestinians. In other words, why has the country maintained a foreign policy of following in suit of the United States (US), its former colonizer, in its support towards Israel? Moreover, what impact has this policy had on the Philippines' role in the international system? Using a constructivist lens, we critically review historical events to analyze the origins, components and implications of Philippine political identities, which then inform foreign policy decisions. In order to answer these questions, we first conceptualize the Philippines’ political identities focusing on two streams: nationalist and neo-imperialist. We then argue that the neo-imperialist current, made possible by the collusion of domestic political elites with the US, has facilitated a foreign policy that results in entrenched dependency on the US where the Philippines follows the dominant discourse dictated by the US on issues such as the Palestine-Israel conflict. This dependency has resulted in a vicious cycle where the Philippines suffers from a diminished role in the international stage through the depletion of its moral capital; in turn, reinforcing dependency. Examining this question is significant not just because of moral reasons but also because of the direct implications on the Philippines’ ability to exercise autonomy and use its power internationally. We adopt a multi-method approach consisting of historical analysis, process-tracing, and discourse analysis to trace the genealogy and contours of these identities.